Pentingnya Metode Mengajar Bagi Guru Sekolah Minggu: Refleksi Injil Markus - Nelly; Siska Siahaan (Vox Dei: Jurnal Teologi dan Pastoral, 2023)
Sunday School or what is known as children's ministry is a service provided by the church to children, aimed at developing strong faith from an early age, introducing Jesus Christ as Lord and Savior. Therefore Sunday School teachers have a big duty and responsibility in serving children. One of the things that need to be prepared is the method of teaching in conveying God's word. The purpose of this study is to describe the importance of teaching methods for Sunday school teachers, the study of reflection on the Gospel of Mark. By using the descriptive analysis method on the Gospel of Mark, it is concluded that the parable, lecture, discussion, and question and answer methods can be used in various ways by Sunday School teachers in conveying God's word so that they can stimulate children's interest, attention, and understanding in learning.